A multi-methodological design framework for roadway illumination - AKGÜN, İLKER; USTAOĞLU, ERHAN (My University, 2022)
Designing the most efficient roadway illumination is a strategic and complex activity, as it requires consideration of both environmental and economic factors. The aim of this study is to propose a novel structured multi-methodological framework based on the systematic application of data envelopment analysis (DEA), quality function deployment (QFD), and simple additive weighting (SAW) methods to support a critical decision-making process on roadway illumination design. First, the DEA is exercised to find efficient alternatives for roadway illumination. Then customer requirements are included and satisfied by the QFD. Lastly, using the DEA method, the SAW is used to rank the alternatives which are found to be efficient. As a case study, illumination alternatives for a typical urban roadway are analysed to select the most suitable choice in terms of energy and cost effectiveness, which are of course high priorities. The results show that the proposed multi-methodological approach takes advantages of DEA, QFD, and SAW to select an efficient roadway illumination alternative. The proposed approach also supplies a simple and very well-suited decision-making tool for this type of strategic decision-making issue. © 2022, LLC Editorial of Journal ""Light Technik"". All rights reserved.
Keywords: Sosyal ve Beşeri Bilimler; Mühendislik ve Teknoloji; Social Sciences and Humanities; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Engineering, Computing & Technology (ENG); Social Sciences (SOC); data envelopment analysis; multi-criteria decision making; quality function deployment; roadway illumination; simple additive weighting